On Inequalities of Lyapunov for Two-Dimensional Nonlinear Dynamic Systems on Time Scales - Qiao-Luan Li; Wing-Sum Cheung; Xu-Yang Fu (Abstract and Applied Analysis, 2013)
We establish some new Lyapunov-type inequalities for two-dimensional nonlinear dynamic systems on time scales. As for application, boundedness of the Emden-Fowler-type equation is proved.